Taking Situatedness Seriously. Embedding Affective Intentionality in Forms of Living - von Maur, Imke (Frontiers in Psychology, 2021)
Situated approaches to affectivity overcome an outdated individualistic perspective on emotions by emphasizing the role embodiment and environment play in affective dynamics. Yet, accounts which provide the conceptual toolbox for analyses in the philosophy of emotions do not go far enough. Their focus falls (a) on the present situation, abstracting from the broader historico-cultural context, and (b) on adopting a largely functionalist approach by conceiving of emotions and the environment as resources to be regulated or scaffolds to be used. In this paper, I argue that we need to take situatedness seriously: We need (a) to acknowledge that emotions are not situated in undetermined “contexts” but in concrete socio-culturally specific practices referring to forms of living; and (b) to agree that not only are context and emotions used for the sake of something else but also that the meaning-disclosive dimension of affective intentionality is structured by situatedness as well. To do so, I offer a multidimensional approach to situatedness that integrates the biographical and cultural dimensions of contextualization within the analysis of situated affective dynamics. This approach suggests that humans affectively disclose meaning (together) which is at once product and producer of specific forms of living – and these are always already subjects of (politically relevant) critique.